The Trade Effects of Regional Agreements and Economic Integration Processes in Europe, South America, and North America - Lopez, Oscar David; Carvajal, Alexander (Latin American Journal of Trade Policy, 2020)
This article seeks to understand the effects of trade creation and diversion in regional agreements and integration processes in Europe, South America, and North America. Through a systemic literature review, and based on the economic theory of integration, it analyzes the impact of tariff barriers on trading volume through the world, as well as the impact of barriers removals in member and non-member countries that participate in these trade agreements. As hypothesis, it can be stated that the trade effects generated by economic integration processes vary depending on the endogenous conditions of the industries in member countries, in addition to the consolidation phase of the integration processes. For this purpose, a qualitative descriptive methodology, based on an analysis of literature, is used to determine the trade creation and deviation effects of agreements in Europe (European Union), South America (MERCOSUR and CAN), and North America (NAFTA).